2020
DOI: 10.31236/osf.io/cj379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mat Pilates as a new approach for breast cancer patients undergoing hormone therapy: a randomized controlled clinical trial study protocol (HAPiMat Study)

Abstract: Introduction: Breast cancer and its treatments lead to several physical and psychological repercussions in the short and long term. Furthermore, breast cancer survivors (BCS) tend to present sedentary behavior, which worsens the aforementioned breast cancer treatment side effects. Physical exercise has been demonstrated to be effective for improving physical and psychological BCS aspects. Therefore, the purpose of this study is to investigate the effects of 24 weeks of supervised Mat Pilates on force productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 40 publications
(56 reference statements)
0
4
0
Order By: Relevance
“…The aim of this study was to analyze the influence of mat Pilates training adherence on muscle strength and flexibility, which was a secondary analysis of the HAPiMat study ( Bertoli et al, 2020 ; Bertoli et al, 2022a ). The results showed that the group with lower training adherence presented increased hip torque variables and left handgrip strength, while the group with higher training adherence presented improved left shoulder abductor TF max and RFI, and left and right upper and lower body flexibility after 24 weeks of intervention.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The aim of this study was to analyze the influence of mat Pilates training adherence on muscle strength and flexibility, which was a secondary analysis of the HAPiMat study ( Bertoli et al, 2020 ; Bertoli et al, 2022a ). The results showed that the group with lower training adherence presented increased hip torque variables and left handgrip strength, while the group with higher training adherence presented improved left shoulder abductor TF max and RFI, and left and right upper and lower body flexibility after 24 weeks of intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The participant recruitment started in February of 2019. The research protocol was published as a preprint with open access ( Bertoli et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations